2000
DOI: 10.1243/1468087001545100
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analyses of the combustion process in a direct injection gasoline engine

Abstract: Gasoline direct injection (GDI) spark ignition engine technology is advancing at a rapid rate. The development and optimization of GDI engines requires new experimental methods and numerical models to analyse the in-cylinder processes. Therefore the objective of this paper is to present numerical and experimental methods to analyse the combustion process in GDI engines. The numerical investigation of a four-stroke three-valve GDI engine was performed with the code KIVA-3V [1]. For the calculation of the turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There may also be contributions from CO 2 * in the spectrum and thus the temperature may be slightly overestimated. Stojkovic et al [22] measured the soot temperature with two-colour pyrometry in stratified operation and found it ranged between 2000 and 2400 K. Similar temperatures were also found by Reissing et al [21], who determined the temperature from the emission lines of sodium (Na) and potassium (K) atoms that were added to the fuel. They showed that the temperature increased with engine speed and load.…”
Section: Optical Measurementsmentioning
confidence: 59%
See 2 more Smart Citations
“…There may also be contributions from CO 2 * in the spectrum and thus the temperature may be slightly overestimated. Stojkovic et al [22] measured the soot temperature with two-colour pyrometry in stratified operation and found it ranged between 2000 and 2400 K. Similar temperatures were also found by Reissing et al [21], who determined the temperature from the emission lines of sodium (Na) and potassium (K) atoms that were added to the fuel. They showed that the temperature increased with engine speed and load.…”
Section: Optical Measurementsmentioning
confidence: 59%
“…The combustion consisted of both premixed flames under lean conditions and fuel-rich flames. Reissing et al [21] performed both experimental investigations and numerical analysis of GDI combustion. In their study, they used spectroscopic data to calculate the fuel-air equivalence ratio (u) near the spark plug as a function of CAD for stratified combustion.…”
Section: Engine Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Calculations at higher engine speeds showed that further development of the ignition and combustion model is necessary for the simulation of the combustion process at higher engine speeds. Further investigations showed that the use of the combustion model for the calculation of the partially premixed combustion in a Gasoline Direct Injection Spark-Ignition engine also seems to be very promising [17]. At the "Institut für Kolbenmaschinen" of the University of Karlsruhe this work is currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…The computational methods presented above for the study of ICE-related flows benefited directly or indirectly from pioneer initiatives that created frameworks to enable the development of novel engine designs. The first big initiative was the development of the KIVA software, 2325 which originally relied on a RANS/LPT approach. The first version of the code was an adaptation of a reactive fluid dynamics code capable of calculations only in two dimensions and with fixed boundary conditions.…”
Section: Introductionmentioning
confidence: 99%